Software testing techniques: a literature review - Jamil, Muhammad Abid; Arif, Muhammad; Awang Abu Bakar, Normi Sham; Ahmad, Akhlaq (IEEE, 2016)
With the growing complexity of today’s software applications injunction with the increasing competitive pressure has pushed the quality assurance of developed software towards new heights. Software testing is an inevitable part of the Software Development Lifecycle, and keeping in line with its criticality in the pre and post development process makes it something that should be catered with enhanced and efficient methodologies and techniques. This paper aims to discuss the existing as well as improved testing techniques for the better quality assurance purposes.